PERFORMANCE OF DRY HYDROPONIC SYSTEM ON CULTIVATION OF GREEN LETTUCE (Lactuca sativa L.) - Sugeng Triyono; Roni Agung Laksono; Ahmad Tusi (Jurnal Ilmiah Rekayasa Pertanian dan Biosistem, 2021)
Dry hydroponic is an emerging system and gaining popularity among some hydroponic businesses, yet investigation on its performance has not been reported. Purpose of this research is to evaluate and compare performance of dry hydroponic system to floating and wick systems on green leafy lettuce cultivation. The experiment used Completely Randomized Design (CRD) with factorial arrangement. Two factors, hydroponic systems and aerator usages, were implemented. The hydroponic systems included Dry, Wick and Floating systems, while the use of aerator were with and without aerators. All treatment combinations consisted of 3 replicates. Parameters to be observed were nutrient solution parameters (pH, temperature, dissolved oxygen, water consumption), plant parameters (height, stem diameter, leaf width, number of leaves, leaf thickness, and canopy area, shoot fresh weight, water content, some chemical contents). Data sets were analyzed using analysis of variance followed by a least significant Difference (LSD) test at level of 5%. Results showed that the interaction between the hydroponic system and the use of aerators were not significantly different for all parameters observed. The hydroponic systems were not significantly different too. The use of aerator was significant for the nutrient solution parameters (pH and Dissolved Oxygen), water content, and phosphorus contents of leaves. In conclusion, Dry Hydroponic System has the same performances as compared to floating and wick systems.